The park never born: Outcome of a quarter of a century of inaction on the sea‐floor integrity of a proposed but not established Marine Protected Area. Issue 5 (25th June 2018) - Bianchi, Carlo Nike; Cocito, Silvia; Diviacco, Giovanni; Dondi, Nicolò; Fratangeli, Francesca; Montefalcone, Monica; Parravicini, Valeriano; Rovere, Alessio; Sgorbini, Sergio; Vacchi, Matteo; Morri, Carla
Abstract: Marine Protected Areas (MPAs) are a major tool to conserve marine ecosystems but are also strongly attractive to tourists, the increased numbers of which can cause environmental issues if not properly managed. Proposing an MPA and then failing to establish it risks advertising the beauty of a marine area without managing the unavoidable increase in tourism. This is what happened at Gallinara Island (Ligurian Sea, north‐western Mediterranean), where an MPA was proposed in 1990 but has not yet been established. Benthic data collected soon after the proposal (1990–92) have been compared with similar information obtained in subsequent periods (2009 and 2016): change has been assessed both visually and statistically, using multivariate and univariate techniques. The Gallinara sea floor supported five epibenthic communities in 1991, four of which corresponded to European Nature Information System (EUNIS) habitats; the fifth epibenthic community, characterized by the erect sponge Axinella polypoides, should be included in the next revision of EUNIS. In the 25 years since the original MPA proposal, all epibenthic communities have exhibited a reduction in their three‐dimensional structure and biotic homogenization, and severe decreases in species diversity, and the sea floor has been littered with derelict fishing gear and other waste from boats. In absence of the MPA, proposals to develop a management plan for a marine Site of Community Importance (SCI) have been provided, to reduce sea‐based human pressures. The dramatic alteration of Gallinara sea floor after 25 years of negligence and inaction is a sad warning for other unmanaged yet beautiful natural areas within urbanized regions of the world.